Career camp : elevating expectations for college-going and career self-efficacy in urban middle school students - Hamel, Julie (Kansas State University, 2014)
Many efforts have been directed towards providing equitable access to higher education for youth from low-income, first-generation families. Despite gains, attendance and graduation rates from college are consistently lower for these students (U.S. Department of Education National Center for Education Statistics, 2012). A variety of initiatives have been implemented to support students' entry into college, persistence to graduation, and increased access to professional careers. One such program is Talent Search, which provides middle school students opportunities to achieve academic success and to become knowledgeable about college and career options. KU Talent Search offers a summer career camp as part of its programming. The Career Horizons Summer Program (CHSP) exists to help students between 6th and 7th grades explore career possibilities, build potential for success in academics and careers, and become more comfortable in a college environment (Dukstein, 2012b). This study examined beliefs about college and careers in a group of 52 students, as well as the impact of the CHSP on the intervention group. Educational aspirations and expectations, and career and college-going self-efficacy were assessed. It was predicted that participation in the camp would result in an increase in college-going and career self-efficacy. The study also provided additional insight into the construct of college-going self-efficacy. Using a quantitative comparison group design, data were collected from camp participants and from students who were eligible to participate but did not. Pre and posttest surveys assessed educational aspirations and expectations and included scales to measure career self-efficacy (Fouad & Smith, 1997) and college-going self-efficacy (Gibbons & Borders, 2010a). Educational aspirations and expectations were high in all participants and a bivariate correlation analysis revealed that career self-efficacy and college-going self-efficacy were highly correlated. Comparisons between the intervention and the comparison group suggested that the CHSP did have an impact on career and college self-efficacy. It is important to understand the characteristics of a successful college and career access program, and to identify interventions that are most impactful. The findings of this study add to understanding of one such intervention and may have implications for specific practices that can increase potential for college success.
Keywords: College; Career Self-Efficacy; Middle School; Educational Aspirations; Educational Expectations; School Counseling (0519)